Preparation of Magnetic Dextran-Mitomycin C Prodrug Conjugate and Its in vivo Antitumor Activity - Yan, Xi-Qing; Lv, Jie-Li; Ai, Fang; Yang, Jun; Xu, Ping; Qiu, Pei-Yong; Jiang, Qing-Feng (Asian Journal of Chemistry, 2013)
As a broad spectrum and strong cytotoxicity against human neoplastic diseases, mitomycin C (MMC)'s clinical use was greatly restricted for its indiscriminate action on tumor and normal cell. This paper proposed the work to devise magnetic targeted mitomycin C conjugate nanoparticles by arbodiimide-catalyzed reaction, so as to the mitomycin C could be release mostly in targeted issues. The properties of magnetic fluid (MF), dextran encapsulated magnetic (DM) and mitomycin C conjugate nanoparticles (MMC-DM) were characterized by Fourier transform infrared, X-ray diffraction, transmission electron microscope, laser particle analyzer and magnetometer. The drug release experiment was conducted at 37 ºC in phosphate buffer solution (pH 7.4) on dissolution. The grafting ratio and drug loading were determined by gel chromatograph spectrophotometry. The in vivo antitumor experiment was carried out in BACA/C nude mice. The results showed that (1) the average diameter of the magnetic conjugate nanoparticles was ca. 125 nm, (2) the mitomycin C in the MMC-DM nanoparticles exhibited extended release in vitro release experiment and (3) the obvious inhibition of the growth of tumor implied that the active ingredient in the magnetic conjugate could be led to the aimed site and decrease damage to normal issues.